2015
DOI: 10.3390/s151229872
|View full text |Cite
|
Sign up to set email alerts
|

Multidirectional Image Sensing for Microscopy Based on a Rotatable Robot

Abstract: Image sensing at a small scale is essentially important in many fields, including microsample observation, defect inspection, material characterization and so on. However, nowadays, multi-directional micro object imaging is still very challenging due to the limited field of view (FOV) of microscopes. This paper reports a novel approach for multi-directional image sensing in microscopes by developing a rotatable robot. First, a robot with endless rotation ability is designed and integrated with the microscope. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…The nanopositioner's movement mechanism is slip-stick mechanism. 24 The details of the rotation robot's shape, structure, technical specifications, and other parameters can be found in the study by Shen et al 23 The rotation robot would rotate so that samples can be observed from different directions. However, when samples are not on the rotation axis of the miniature robot, samples Figure 1, the relative position between samples and rotation axis is calculated based on sample's position shift on microscope images during miniature robot and sample's rotation.…”
Section: Principle Of the Alignment Angle-based Alignmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The nanopositioner's movement mechanism is slip-stick mechanism. 24 The details of the rotation robot's shape, structure, technical specifications, and other parameters can be found in the study by Shen et al 23 The rotation robot would rotate so that samples can be observed from different directions. However, when samples are not on the rotation axis of the miniature robot, samples Figure 1, the relative position between samples and rotation axis is calculated based on sample's position shift on microscope images during miniature robot and sample's rotation.…”
Section: Principle Of the Alignment Angle-based Alignmentmentioning
confidence: 99%
“…The relative position between samples and rotation axis would be calculated based on those three coordinates. 23 Suppose that a point on the sample has coordinate ðx N ; y N ; z N Þ in fNg and the same point has the coordinate ðx M ; y M ; z M Þ in fMg, then the following equation can be achieved 25 x M y M z M …”
Section: Principle Of the Alignment Angle-based Alignmentmentioning
confidence: 99%
See 3 more Smart Citations